Extensive remodeling of sugar metabolism through gene loss and horizontal gene transfer in a eukaryotic lineage - Ana Pontes; Francisca Paraíso; Margarida Silva; Catarina Lagoas; Andreia Aires; Patrícia H. Brito; Carlos A. Rosa; Marc-André Lachance; José Paulo Sampaio; Carla Gonçalves; Paula Gonçalves (BMC Biology, 2024)
Abstract Background In yeasts belonging to the subphylum Saccharomycotina, genes encoding components of the main metabolic pathways, like alcoholic fermentation, are usually conserved. However, in fructophilic species belonging to the floral Wickerhamiella and Starmerella genera (W/S clade), alcoholic fermentation was uniquely shaped by events of gene loss and horizontal gene transfer (HGT). Results Because HGT and gene losses were first identified when only eight W/S-clade genomes were available, we collected publicly available genome data and sequenced the genomes of 36 additional species. A total of 63 genomes, representing most of the species described in the clade, were included in the analyses. Firstly, we inferred the phylogenomic tree of the clade and inspected the genomes for the presence of HGT-derived genes involved in fructophily and alcoholic fermentation. We predicted nine independent HGT events and several instances of secondary loss pertaining to both pathways. To investigate the possible links between gene loss and acquisition events and evolution of sugar metabolism, we conducted phenotypic characterization of 42 W/S-clade species including estimates of sugar consumption rates and fermentation byproduct formation. In some instances, the reconciliation of genotypes and phenotypes yielded unexpected results, such as the discovery of fructophily in the absence of the cornerstone gene (FFZ1) and robust alcoholic fermentation in the absence of the respective canonical pathway. Conclusions These observations suggest that reinstatement of alcoholic fermentation in the W/S clade triggered a surge of innovation that goes beyond the utilization of xenologous enzymes, with fructose metabolism playing a key role.